Stopwatch Verification Platform The Development Of An Automated Device For Stopwatch Calibration - Karis, Mohd Safirin; Hasim, Norhaslinda; Zainal Abidin, Amar Faiz; Sulaiman, Siti Fatimah (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Stopwatch is designed to quantify the elapses time between the start activation and deactivation. To ensure the precision of the time taken, calibration of the device is essential. National Institute of Standard and Technology (NIST) has provide complete guidelines on the stopwatch and timer calibration. However, the standards guidelines usually use manual calibration personnel hence may possibly cause inefficiency for calibration works. The 'Stopwatch Verification Platform' is a prototype aimed to replace the manual handling of digital stopwatch calibration with an automated timer-controlled device, without interfering with NIST recommended practice. The 'Stopwatch Verification Platform' is able to automatically trigger start and stop the reference and test stopwatches by integrating with precise timer controller and specific relay connections. The timer controller circuitry is integrated with the reference stopwatch circuitry, with 0.001 second resolutionIt is capable in verifying more units of stopwatches by using one reference. The measurement procedures do not contradict with the NIST recommended practice. This prototype does not alter the uncertainties calculation because it is a well-developed standard formula which is set by international standard.